2018
DOI: 10.2147/copd.s152291
|View full text |Cite
|
Sign up to set email alerts
|

Role of eosinophils in airway inflammation of chronic obstructive pulmonary disease

Abstract: COPD is a significant cause of morbidity and mortality. In some patients with COPD, eosinophils contribute to inflammation that promotes airway obstruction; approximately a third of stable COPD patients have evidence of eosinophilic inflammation. Although the eosinophil threshold associated with clinical relevance in patients with COPD is currently subject to debate, eosinophil counts hold potential as biomarkers to guide therapy. In particular, eosinophil counts may be useful in assessing which patients may b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
121
0
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 140 publications
(129 citation statements)
references
References 122 publications
(195 reference statements)
3
121
0
5
Order By: Relevance
“…Skin bruising and oral candidiasis were increased with ICS therapy in most studies 7,8,10,43,58. In a subset of patients from the Lung Health Study, no effect of ICSs on adrenal function was observed over the 3-year study duration 59.…”
Section: Safety Considerationsmentioning
confidence: 95%
See 1 more Smart Citation
“…Skin bruising and oral candidiasis were increased with ICS therapy in most studies 7,8,10,43,58. In a subset of patients from the Lung Health Study, no effect of ICSs on adrenal function was observed over the 3-year study duration 59.…”
Section: Safety Considerationsmentioning
confidence: 95%
“…Moreover, therapeutic agents targeting eosinophils, namely anti-IL5 and anti-IL5-receptor monoclonal antibodies, have been evaluated to reduce the risk of exacerbations in COPD patients with high eosinophil counts and a history of exacerbations despite optimized standard-of-care therapy;43 however, results have been inconsistent 93–95…”
Section: Future Directions: Triple Therapy and Beyondmentioning
confidence: 99%
“…In recent years, amount of studies showed that blood eosinophil is an effective, stable, and available biomarker in COPD, which can be used to de ne the phenotypes of COPD [17,25,34,35]. However, the cut-off value of blood EOS is still in debate, ranging from 150 to 400 cells/μL and/or 2% to 4% in different studies [17,18,22,24,25,[34][35][36]. Then, in this study, both 200 cells/μL and 300 cells/ μL, and, 2% and 3% were considered as the cut-off values of blood EOS counts and EOS% in AECOPD patients (Figure 1).…”
Section: Discussionmentioning
confidence: 99%
“…Many studied showed that blood EOS was considered to be a reasonably good predictor of EOS in airways in COPD patients [22,37,38]. Eltboli O et al showed that the strong correlations between blood EOS% and the submucosal eosinophil counts (r = 0.57) and reticular basement membrane (RBM) thickness (r = 0.59) were found in COPD [37].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation